1994
DOI: 10.1016/0169-7439(94)85042-9
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria steepest ascent

Abstract: A simple multiresponse steepest ascent procedure has been developed by combining the standard steepest ascent method with multicriteria decision making. The steepest ascent method is one of the older methods in response surface methodology. It can be applied in optimization where the operability region is so large that a very complex function would be needed to fit an empirical function. With steepest ascent, local designs and local models in a part of the operability region are used to find a .direction where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Duineveld et al (1994) illustrated this for a particular case and showed how a search direction can be PO for some step sizes but not for others. Although many of the methods proposed herein depend on the simplicity of the first-order model, the concept of "paths of improvement" regions does not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duineveld et al (1994) illustrated this for a particular case and showed how a search direction can be PO for some step sizes but not for others. Although many of the methods proposed herein depend on the simplicity of the first-order model, the concept of "paths of improvement" regions does not.…”
Section: Discussionmentioning
confidence: 99%
“…In Section 3 we formally define PO treatment combinations and show which points are PO for the first-order model. Duineveld et al (1994) presented examples of PO points lying a fixed distance from the design center for both first-order and more complex models. Using either overlaid contour plots or sets of PO predictions, we can compare the options and select a suitable compromise.…”
Section: Multiple-response Optimization Literaturementioning
confidence: 99%